Considerate Equilibrium - Vöcking, Berthold; Hoefer, Martin; Skopalik, Alexander; Penn, Michal; Polukarov, Maria (IJCAI 2011, Proceedings of the 22nd International Joint Conference on Artificial Intelligence,)

Mechanical and Physical Properties - A Way to asses quality of Laser Sintered Parts - Rüsenberg, Stefan; Schmidt, L.; Schmid, Hans-Joachim (22th Annual International Solid Freeform Fabrication Symposium)
The aim of this paper is the description and evaluation of physical properties like porosity and density and their influence on mechanical properties of laser sintered polyamide parts. For example, by reducing the porosity an increase of mechanical properties is possible. The correlation of laser parameters to these properties is investigated in detail. The energy density is an important parameter for the laser sintering process. By changing laser power, scan velocity and hatch distance an influence on manufactured components is given. A systematic variation of all three laser parameters is performed. A comparison of results obtained at constant energy densities obtained by varying these relevant parameters accordingly is shown as well.

Porosity as a key to increase material properties of laser sintered parts - Rüsenberg, Stefan; Schmidt, L.; Hosse, H.; Schmid, Hans-Joachim

Direct Manufacturing Design Rules - Adam, Guido; Zimmer, Detmar

Steigerung der Anlagenverfügbarkeit von Antriebssystemen durch methodische und modulare Konzeption. Modulare Konzeption von als Einzelstücke oder in Kleinserien hergestellten Antriebssystemen mit großer Nennleistung - Fiekens, Nicolas; Zimmer, Detmar (VDI/VDE-Tagung mit Fachausstellung Antriebssysteme 2011. Elektrik, Mechanik und Hydraulik in der Anwendung)

DMDR Direct Manufacturing Design Rules. Erarbeiten von applikationsunabhängigen Konstruktionsregeln - Zimmer, Detmar; Adam, Guido (Rapid.Tech 2011 Fachmesse und Anwendertagung für Rapid-Technologie)

Bestimmung der Biegesteifigkeit eines Schubgliederbandes - Zimmer, Detmar; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Hybrid Planning for Self-Optimization in Railbound Mechatronic Systems - Adelt, Philipp; Esau, Natascha; Hölscher, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Zimmer, Detmar

Component-Based Hazard Analysis for Mechatronic Systems - Priesterjahn, Claudia; Sondermann-Wölke, Christoph; Tichy, Matthias; Hölscher, Christian (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

MID-Marktanalyse: Schwerpunkte und Chancen von MID - Franke, Joerg; Dumitrescu, Roman; Gausemeier, Jürgen; Goth, Christian (Sonderausgabe Räumliche elektronische Baugruppen, Fachzeitschrift Elektronik)

Integrative Development of Product and Production System - Gausemeier, Jürgen; Dumitrescu, Roman; Kahl, Sascha; Nordsiek, Daniel (Robotics and Computer Integrated Manufacturing 27(4))

Laser-sintered platform with optical sensor for a mobile robot used in cooperative load transport - Loh, Chia Choon; Trächtler, Ansgar (accepted for publication at 37th Annual Conference on IEEE Industrial Electronics Society (IECON))

Mehrzieloptimierung zur Stellgrößenermittlung für die Horizontaldynamik eines Elektrofahrzeugs mit Einzelradaktorik - Reinold, Peter; Trächtler, Ansgar (Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG 2011)

Differential Dynamic Programming and the Optimal Control of Vehicle Lateral Dynamics - Khatab, Shaady; Trächtler, Ansgar (Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG 2011)

Entwurfstechnik Intelligente Mechatronik - Tichy, Matthias; Oestersötebier, Felix; Schierbaum, Thomas (Internationales Forum Mechatronik)

Parametric Model-Order Reduction in Hierarchical Multiobjective Optimization of Mechatronic Systems - Krüger, Martin; Witting, Katrin; Trächtler, Ansgar; Dellnitz, Michael (18th IFAC World Congress)

Iterative learning of Stochastic Disturbance Profiles Using Bayesian Networks - Bielawny, Dirk; Krüger, Martin; Reinold, Peter; Timmermann, Julia; Trächtler, Ansgar (9th International Conference on Industrial Informatics (INDIN))

Fast Pareto set computation using algorithmic differentiation applied to the guidance of a rail-bound vehicle - Witting, Katrin; Dellnitz, Michael; Geisler, Jens; Trächtler, Ansgar; Walther, Andrea (International Conference on Simulation Technology – SIMTECH)

Verlässlichkeitsanalyse des Degradationsverhaltens mechatronischer Systeme mit mehreren Betriebsstrategien - Lurye, Oleg; Sondermann-Wölke, Christoph; Kromov, Ivan; Sextro, Walter; Trächtler, Ansgar (VDI Bericht zur Tagung Technische Zuverlässigkeit)

Multidomänen-Modell eines Waschvollautomaten für einen Hardware-in-the-Loop-Prüfstand - Löffler, Alexander; Schweers, Christoph; Fast, Viktor; Kruse, Daniel; Trächtler, Ansgar (8. Paderborner Workshop: "Entwurf mechatronischer Systeme")